Comprehensive stroke units: a review of comparative evidence and experience. Issue 4 (19th July 2012) - Chan, Daniel K. Y.; Cordato, Dennis; O'Rourke, Fintan; Chan, Daniel L; Pollack, Michael; Middleton, Sandy; Levi, Chris
<x xml:space="preserve">Abstract</x> Background Stroke unit care offers significant benefits in survival and dependency when compared to general medical ward. Most stroke units are either acute or rehabilitation, but comprehensive (combined acute and rehabilitation) model (comprehensive stroke unit) is less common. Aim To examine different levels of evidence of comprehensive stroke unit compared to other organized inpatient stroke care and share local experience of comprehensive stroke units. Methods Cochrane Library and Medline (1980 to December 2010) review of English language articles comparing stroke units to alternative forms of stroke care delivery, different types of stroke unit models, and differences in processes of care within different stroke unit models. Different levels of comparative evidence of comprehensive stroke units to other models of stroke units are collected. Results There are no randomized controlled trials directly comparing comprehensive stroke units to other stroke unit models (either acute or rehabilitation). Comprehensive stroke units are associated with reduced length of stay and greatest reduction in combined death and dependency in a meta‐analysis study when compared to other stroke unit models. Comprehensive stroke units also have better length of stay and functional outcome when compared to acute or rehabilitation stroke unit models in a cross‐sectional study, and better length of stay in a 'before‐and‐after' comparative study. Components of stroke unit care that improve outcome are multifactorial and most probably include early mobilization. A comprehensive stroke unit model has been successfully implemented in metropolitan and rural hospital settings. Conclusions Comprehensive stroke units are associated with reductions in length of stay and combined death and dependency and improved functional outcomes compared to other stroke unit models. A comprehensive stroke unit model is worth considering as the preferred model of stroke unit care in the planning and delivery of metropolitan and rural stroke services.